Depth alone is an inappropriate proxy for physiological change in the mesophotic coral Agaricia lamarcki. (24th June 2019) - Laverick, Jack H.; Green, Tamara K.; Burdett, Heidi L.; Newton, Jason; Rogers, Alex D.
Abstract: The physiology of mesophotic Scleractinia varies with depth in response to environmental change. Previous research has documented trends in heterotrophy and photosynthesis with depth, but has not addressed between-site variation for a single species. Environmental differences between sites at a local scale and heterogeneous microhabitats, because of irradiance and food availability, are likely important factors when explaining the occurrence and physiology of Scleractinia. Here, 108 colonies of Agaricia lamarcki were sampled from two locations off the coast of Utila, Honduras, distributed evenly down the observed 50 m depth range of the species. We found that depth alone was not sufficient to fully explain physiological variation. Pulse Amplitude-Modulation fluorometry and stable isotope analyses revealed that trends in photochemical and heterotrophic activity with depth varied markedly between sites. Our isotope analyses do not support an obligate link between photosynthetic activity and heterotrophic subsidy with increasing depth. We found that A. lamarcki colonies at the bottom of the species depth range can be physiologically similar to those nearer the surface. As a potential explanation, we hypothesize sites with high topographical complexity, and therefore varied microhabitats, may provide more physiological niches distributed across a larger depth range. Varied microhabitats with depth may reduce the dominance of depth as a physiological determinant. Thus, A. lamarcki may 'avoid' changes in environment with depth, by instead existing in a subset of favourable niches. Our observations correlate with site-specific depth ranges, advocating for linking physiology and abiotic profiles when defining the distribution of mesophotic taxa.